Financing the Green Transition: The Role of Green Bonds in Renewable Electricity Expansion - Fabiański, Szymon; Kębłowski, Piotr (Central European Journal of Economic Modelling and Econometrics, 2025)
This study examines the interplay between monetary policy and the deployment of renewable electricity in Europe, addressing gaps in the existing literature. Against the backdrop of escalating greenhouse gas emissions, the paper examines the impact of monetary policy on the development of green energy infrastructure. By examining various determinants influencing the deployment of renewable electricity, the study identifies a novel area, the relationship between monetary policy and the evolving energy landscape characterised by increased private sector involvement and a shift from consumers to ’prosumers’. Using a pan-European approach from 2008 to 2022, the research poses two key questions: (1) Are interest rate movements associated with variations in renewable electricity deployment across different forms of renewable electricity generation? (2) Does the level of private sector involvement contribute to heterogeneity in the impact of monetary policy? The study uses rigorous panel analysis to unravel these dynamics, providing insight into the critical factors shaping the future trajectory of green energy in Europe. This research contributes to understanding the nuanced drivers of renewable electricity deployment and informs policymakers, researchers, and stakeholders working towards a sustainable energy transition.